Geosynthetics: Microstructure and Performance 1990
DOI: 10.1520/stp23499s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geotextile Structure on Pore Size Determination

Abstract: Filtration performance of a geotextile is related to its capacity to retain soil particles over time without clogging. A pore size determination such as the filtration opening size (FOS) is used to assess the geotextile's filtration behavior. Standard hydrodynamic methods use a soil with a uniformity coefficient (Cu) greater than 6, with the coarser particle size value at least twice the estimated FOS value, and with a d10 four times smaller than the FOS value. The filtration opening size determination, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…where d f = fiber thickness; n = porosity; t = geotextile thickness; = dimensionless parameter; and O f = filtration opening size and is usually given by the nearly largest constriction size of a particular geotextile (e.g., C 95 ). Comparisons of with the data of 52 laboratory tests published by Rigo et al (1990) indicated that the use of = 10 is reasonable (Giroud 1996). The fiber thickness ͑d f ͒ was measured from the captured images and an equation given by Wayne and Koerner (1993) was used to determine the porosity ͑n͒…”
Section: Comparison Of Predicted Constriction Sizes With Theoretical mentioning
confidence: 94%
“…where d f = fiber thickness; n = porosity; t = geotextile thickness; = dimensionless parameter; and O f = filtration opening size and is usually given by the nearly largest constriction size of a particular geotextile (e.g., C 95 ). Comparisons of with the data of 52 laboratory tests published by Rigo et al (1990) indicated that the use of = 10 is reasonable (Giroud 1996). The fiber thickness ͑d f ͒ was measured from the captured images and an equation given by Wayne and Koerner (1993) was used to determine the porosity ͑n͒…”
Section: Comparison Of Predicted Constriction Sizes With Theoretical mentioning
confidence: 94%
“…The nonwoven geotextile is a highly porous material. Since this material has a wide pore size distribution-between several microns and approximately 300 p m (Silva and Bhatia, 1993;Rigo et al, 1990)-it is expected that different-sized soil particles could be entrapped in these pores, and therefore be fixed in space. (Strictly speaking, nonwoven geotextile has no pores with a determined length and diameter such as are in rigid porous materials like the ones used in catalysis.…”
Section: Immobilized Soil Reactormentioning
confidence: 99%
“…According to Rigo et al (1990) geotextile properties playing an important role in filtration are: fiber diameter, fabric thickness, fabric density (mass per area), fabric porosity and filtration opening size. Among these properties, the opening size has been found in various types of laboratory tests a key parameter in control of geotextile filter performance.…”
Section: Clogging Factors Related To Geotextile Propertiesmentioning
confidence: 99%